Complicaciones obstétricas y factores sociodemográficos en gestantes de edad avanzada en el Hospital Regional de Loreto junio 2020 - junio 2021 - Soto Soria, Christian Ralph (2022)
Introduction: Obstetric complications are present in all age ranges, but with a higher incidence in extreme ages such as pregnant women under 19 years of age and women over 35, however, advanced maternal age is the most populous group at risk. in the region to understand an age range (35-49) that means 19.5% of all pregnancies projected to 2020 in the Loreto region. Objective: To determine obstetric complications and sociodemographic factors in elderly pregnant women at the Regional Hospital of Loreto June 2020 - June 2021. Methodology: Descriptive-correlational, non-experimental and retrospective study with a crosssectional design. It comprises a finite population sample composed of 140 elderly pregnant women. The data collection was from a secondary source. Results: The frequency of elderly pregnant women over 35 years of age is 13.82%. 86.4% presented obstetric complications in 3 moments of pregnancy. Pre-existing diseases: Anemia 55%; history of abortion 45.7%; Previous cesarean section 33.6%. Diseases associated with pregnancy Urinary tract infection UTI 37.9%, preeclampsia 16.4% and gestational hypertension HIE 15.7%. Diseases associated with childbirth and postpartum: Acute fetal distress 15%, prematurity 11.4%, oligohydramnios 10% and prolonged delivery 9.3%. No significant relationship was found between obstetric complications and sociodemographic characteristics. A statistically significant relationship was found between obstetric complications and prenatal care (p = 0.019).